ANALISIS KETERAMPILAN KONEKSI MATEMATIKA DITINJAU DARI GAYA BELAJAR PESERTA DIDIK - Rina Febriana; Hafizah Delyana (Universitas Muhammadiyah Semarang, 2022)
This study aims to describe and analyze students' mathematical connection skills related to learning styles. The research was conducted at SMPN 1 Luhak Nan Duo class VII.a in West Pasaman Regency. The subjects of this study were three students from 30 students of class VII.a with auditory, visual, and kinesthetic sensation learning styles. Qualitative descriptive research method, instrument in the form of a questionnaire to see learning styles and tests of mathematical connection skills. the results of the study concluded that the visual learning style in solving math problems did not use the relationship between mathematical ideas so the indicators of mathematical connection had not been achieved, studeand nts with auditory learning styles did not meet the indicators of mathematical connections related to mathematical ideas using relevant indicators related to mathematics, learning Sensory motor has perfect mathematical connection skills, the ability to generate consistent mathematical ideas.